President of the Republic of Kazakhstan – Fundamental guarantee of observance and protection of human rights and freedoms (Journal of actual problems of jurisprudence, 2018)
The aim is to define the role and significance of the President of Kazakhstan as the main guarantor of the rights and freedoms of citizens in addressing issues and problems holistic integrated development mechanism to guarantee, protect and ensure the rights and freedoms of man and citizen in Kazakhstan. Methodology of work amounted to the dialectical method, the concrete historical, comparative, sociological research methods and the method of modeling and forecasting. Findings and results of the work was to analyze the formation and development of all elements of the constitutional rights and freedoms of citizens, the place and importance of the activities of the President of the Republic of Kazakhstan for the protection of the rights and freedoms of citizens of the Republic of Kazakhstan. The author analyzes the constitutional and legal rights law and freedoms and lead to concrete proposals to improve it. Scope, the results obtained by the author of article, is to improve the constitutional legislation enshrining the rights and freedoms of citizens. The author’s conclusions can be used to improve the mechanism of protection and ensure the rights and freedoms of citizens of Kazakhstan, as well as in teaching law at the constitutional-legal disciplines cycle.Key words: Constitutional rights and freedoms of citizens of Republic of Kazakhstan, President of Republic of Kazakhstan, the guarantor of the rights and freedoms of citizens, the mechanism of protection of the rights and freedoms of citizens.